Improving Cognitive Workload in Radiation Therapists: A Pilot EEG Neurofeedback Study - Campbell, Alana M.; Mattoni, Matthew; Yefimov, Mae Nicopolis; Adapa, Karthik; Mazur, Lukasz M. (Frontiers in Psychology, 2020)
Radiation therapy therapists face challenging daily tasks that leave them prone to high attrition and burnout and subsequent deficits in performance. Here, we employed an accelerated alpha-theta neurofeedback protocol that is implementable in a busy medical workplace to test if 12 radiation therapy therapists could learn the protocol and exhibit behavior and brain performance-related benefits. Following the three-week protocol, participants showed a decrease in subjective cognitive workload and a decrease in response time during a performance task, as well as a decrease in desynchrony of the alpha EEG band. Additionally, novel microstate analysis for neurofeedback showed a significant decrease in global field power following neurofeedback. These results suggest that the radiation therapy therapists successfully learned the protocol and improved in perceived cognitive workload following three weeks of neurofeedback. In sum, this study presents promising behavioral improvements as well as brain performance-related evidence of neurophysiological changes following neurofeedback, supporting the feasibility of implementing neurofeedback in a busy workplace and encouraging the further study of neurofeedback as a tool to mitigate burnout.